2022
DOI: 10.1002/mabi.202200130
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaled PAMAM Dendrimer Spacer Improved the Photothermal‒Photodynamic Treatment Efficiency of Photosensitizer‐Decorated Confeito‐Like Gold Nanoparticles for Cancer Therapy

Abstract: A critical factor in developing an efficient photosensitizer-gold nanoparticle (PS-AuNP) hybrid system with improved plasmonic photosensitization is to allocate a suitable space between AuNPs and PS. Poly(amidoamine) (PAMAM) dendrimer is selected as a spacer between the PS and confeito-like gold nanoparticles (confeito-AuNPs), providing the required distance (≈2.5-22.5 nm) for plasmon-enhanced singlet oxygen generation and heat production upon 638-nm laser irradiation and increase the cellular internalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 91 publications
1
7
0
Order By: Relevance
“…But we found that the lung exhibited stronger fluorescence for free TCPP compared to other organs. Chung et al reported a similar biodistribution pattern for free TCPP . These results were consistent with the in vivo imaging data obtained previously.…”
Section: Resultssupporting
confidence: 90%
“…But we found that the lung exhibited stronger fluorescence for free TCPP compared to other organs. Chung et al reported a similar biodistribution pattern for free TCPP . These results were consistent with the in vivo imaging data obtained previously.…”
Section: Resultssupporting
confidence: 90%
“…In another study, poly­(amidoamine) dendrimers were utilized as spacers between the photosensitizers and gold NPs to provide nanosystems with high phototoxicity toward breast cancerous cell lines including MCF7, 4T1, and MDA-MB-231 (in vitro), showing suitable photothermal/photodynamic combinational therapeutic efficiency. Both in vitro and in vivo studies confirmed the efficacy of these nanosystems for accelerating the cellular uptake, plasmon-boosted singlet oxygen, and heat production …”
Section: Advanced Nanosystems For Targeted Cancer Therapeuticsmentioning
confidence: 68%
“…Both in vitro and in vivo studies confirmed the efficacy of these nanosystems for accelerating the cellular uptake, plasmon-boosted singlet oxygen, and heat production. 77 2.1.3. Monoclonal Antibodies (mAbs) NPs.…”
Section: Advanced Nanosystems For Targeted Cancer Therapeuticsmentioning
confidence: 99%
“…The photothermal therapeutic properties of these nanocomposites could be realized via irradiation of an external light source. [109] Furthermore, other photosensitizers could also be loaded into dendrimers in order to achieve their higher accumulation in tumor cells and efficient release of ROS, which would be precise, safe, and effective means of treatment and remarkably enhance the therapeutic effect of PDT. [110] PDT has become a burgeoning cancer treatment modality with considerable advantages, including minimal side effects, least drug resistance, and negligible systemic toxicity.…”
Section: Dendrimer Conjugates To Enhance Photodynamic Therapymentioning
confidence: 99%